Non-standard Wigner doublets - da Silva Barbosa, F. A.; Hoff da Silva, J. M. [UNESP] (IOP Publishing, 2023)
Guided by a conservative formulation in investigating the physical content of quantum fields, we explore non-standard Wigner classes of particles that could provide the basis for self-interaction models to dark matter. We critically contrast the analysis with long-standing constraints to non-standard Wigner classes in the literature to discuss the model's viability.